Barriers and facilitators to the implementation of antenatal syphilis screening and treatment for the prevention of congenital syphilis in the Democratic Republic of Congo and Zambia: results of qualitative formative research - Dalau Nkamba; Musaku Mwenechanya; Arlette Mavila Kilonga; Maria Luisa Cafferata; Amanda Mabel Berrueta; Agustina Mazzoni; Fernando Althabe; Ezequiel Garcia-Elorrio; Antoniette K. Tshefu; Elwyn Chomba; Pierre M. Buekens; Maria Belizan (BMC, 2017)
Abstract Background The impact of untreated syphilis during pregnancy on neonatal health remains a major public health threat worldwide. Given the high prevalence of syphilis during pregnancy in Zambia and Democratic Republic of Congo (DRC), the Preventive Congenital Syphilis Trial (PCS Trial), a cluster randomized trial, was proposed to increase same-day screening and treatment of syphilis during antenatal care visits. To design an accepted and feasible intervention, we conducted a qualitative  formative research. Our objective was to identify context-specific  barriers and facilitators to the implementation of antenatal screening and treatment during pregnancy. Methods Qualitative research included in-depth semi-structured interviews with clinic administrators, group interviews with health care providers, and focus groups with pregnant women in primary care clinics (PCCs) in Kinshasa (DRC) and Lusaka (Zambia). Results A total of 112 individuals participated in the interviews and focus groups. Barriers for the implementation of syphilis testing and treatment were identified at the a) system level: fragmentation of the health system, existence of ANC guidelines in conflict with proposed intervention, poor accessibility of clinics (geographical and functional), staff and product shortages at the PCCs; b) healthcare providers' level: lack of knowledge and training about evolving best practices, reservations regarding same-day screening and treatment; c) Pregnant women level: late enrollment in ANC, lack of knowledge about consequences and treatment of syphilis, and stigma. Based on these results, we developed recommendations for the design of the PCS Trial intervention. Conclusion This research allowed us to identify barriers and facilitators to improve the feasibility and acceptability of a behavioral intervention. Formative research is a critical step in designing appropriate and effective interventions by closing the "know-do gap".